Cover Picture: Measuring the Relative Reactivity of the Carbon–Hydrogen Bonds of Alkanes as Nucleophiles (Angew. Chem. Int. Ed. 42/2018). Issue 42 (21st September 2018) - Olmos, Andrea; Gava, Riccardo; Noverges, Bárbara; Bellezza, Delia; Jacob, Kane; Besora, Maria; Sameera, W. M. Chamil; Etienne, Michel; Maseras, Feliu; Asensio, Gregorio; Caballero, Ana; Pérez, Pedro J.
Abstract : The relative reactivity of a series of alkane C−H bonds towards silver, copper, and rhodium carbene complexes acting as electrophiles has been studied. In their Communication onpage 13848 ff., P. J. Pérez and co‐workers show that the carbon–hydrogen bond of methane represents the poorest nucleophile and, therefore, sits on top of the ladder. The other bonds studied do not follow the commonly claimed order of reactivity (tertiary>secondary>primary sites), and the reactivity trends do not follow their bond dissociation energies (Cover design: Ivan Rivilla).